Biogels in Soils: Plant Mucilage as a Biofilm Matrix That Shapes the Rhizosphere Microbial Habitat - Nazari, Meisam; Bickel, Samuel; Benard, Pascal; Mason-Jones, Kyle; Carminati, Andrea; Dippold, Michaela A. (Frontiers in Plant Science, 2022)
Mucilage is a gelatinous high-molecular-weight substance produced by almost all plants, serving numerous functions for plant and soil. To date, research has mainly focused on hydraulic and physical functions of mucilage in the rhizosphere. Studies on the relevance of mucilage as a microbial habitat are scarce. Extracellular polymeric substances (EPS) are gelatinous high-molecular-weight substances produced by microorganisms. EPS support the establishment of microbial assemblages in soils called biofilms, mainly through providing a moist environment, a protective barrier, and serving as carbon and nutrient sources. We propose that mucilage shares physical and chemical properties with EPS, functioning similarly as a biofilm matrix covering a large extent of the rhizosphere. Our analyses largely confirmed the hypothesis of similar viscosity and surface tension as important physical properties and polysaccharide, protein, neutral monosaccharide, and uronic acid composition as major chemical properties. Our analyses, and literature review suggest that all major functions known for EPS and required for biofilm formation are also provided by mucilage, offering a protected habitat optimized for nutrient mobilization with mucilage itself functioning as carbon and nutrient source. We suggest that the function of mucilage as a biofilm matrix and prerequisite for high rhizomicrobial abundance and activity has been strongly underestimated, and should be considered in conceptual models of the rhizosphere.